Evaluation of rapid diagnostic tests and Enzyme Linked Immunoassay in the detection of malaria in ancient human remains. (April 2020) - Loufouma-Mbouaka, Alvie; Binder, Michaela; Noedl, Harald; Gamble, Michelle
Abstract: Malaria has had a significant impact on humans for millennia, yet it has proved difficult to conclusively identify. To-date, there is no absolute way to quantify and confirm the presence of malaria in ancient human remains. Clinically, rapid diagnostic tests (RDTs) are regularly used as a cost-effective and efficient method of identifying the presence of Plasmodium parasite antigens (i.e. malaria) in blood samples. In this study, we evaluate two different immunoassay methods used in the detection of malaria antigens on ancient human skeletal remains, utilising the current generation of RDTs, as well as a highly sensitive histidine rich protein 2 double-site sandwich Enzyme Linked Immunoassay (HRP2-ELISA). Our investigation using RDTs and ELISA immunoassay has produced mixed results, providing new input into, and raising questions regarding, the efficacy and reliability of these immunoassays in the detection of the Plasmodium parasite antigens in ancient bones. Specific protocols to adapt the tests to bone samples must be adhered to, and the sensitivity of the test is crucial to identification. Further optimization of these methods would provide a cost effective avenue of conclusively identifying malaria in the past, and should continue to be pursued. We found that the QDx Malaria Card tests DiaSys produced the highest number of positive results, with 50% of the samples testing positive for malaria with these particular tests. Highlights: Biomolecular approaches to identifying malaria on ancient human remains prove challenging. Immunoassays using Rapid Diagnostic Tests and ELISA would be cost-effective methods of identifying ancient malaria. Antigen extraction from bone provides an unknown variable in identification on tests designed for blood samples. Antigen/protein identification on the nitrocellulose strips is needed to provide more certainty and avoid false positives.